Analisis Produksi Penangkapan Ikan Cakalang (Katsuwonus pelamis) di WPPNRI 572 yang Didaratkan di Pelabuhan Perikanan Samudera (PPS) Nizam Zachman Jakarta - Yansen Yosafat; Yusrudin Yusrudin; Sumaryam Sumaryam (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
One of the main problems in the productivity of skipjack tuna (Katsuwonus Pelamis) fishing is overfishing which threatens sustainability. This research was conducted to analyze production activities, utilization levels, and their relationship to the sustainability conditions of skipjack tuna (Katsuwonus Pelamis) originating from the WPPNRI 572 waters which are landed at Oceanic fishery Harbor Nizam Zachman Jakarta. Data obtained from the annual report of Oceanic fishery Harbor Nizam Zachman Jakarta for the last ten years, then the data was processed to obtain CpUE, MSY, JTB, and TP data using the 1954 Schaefer model quantitative descriptive method. Based on the research, data was obtained that the production of skipjack tuna originating from WPPNRI 572 and landed at the Oceanic Fishery Harbor Nizam Zachman Jakarta in the last ten years was 366,677.90 tons with a standard effort of 8.644 trips, a CpUE value of 42,42 tons/trip, an MSY value of 39.208,46 tons/trip, and a maximum JTB value. 31.366,77 tons/trip. Based on this data, it was found that the condition of the skipjack tuna resource originating from WPPNRI 572 was in Fully-exploited status with a condition of 94%.